1989
DOI: 10.3109/00365528909093115
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Polyamine Synthesis by α-Difluoromethylornithine and its Effects on Pancreatic Secretion and Growth in the Rat

Abstract: The role played by the polyamines in mediating the pancreatic growth and secretory responses to hormonal stimulation is uncertain. The effect of an inhibitor of ornithine decarboxylase (ODC), alpha-difluoromethylornithine (DFMO), on rat pancreatic protein secretion and synthesis and on growth in response to hormonal stimulation was therefore studied. Anesthetized rats were given an intravenous injection of DFMO (50, 100, or 150 mg/kg), followed by a 7-h continuous infusion (15, 25, or 35 mg/kg/h, respectively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…It could be shown that neither CCK-LP stimu lated pancreatic volume nor enzyme secre tion could be inhibited by giving simulta neously DFMO [11]. Similar to the studies concerning pancreatic growth, the applica tion of DFMO was not able to reduce the polyamine concentrations under a critical level.…”
Section: Influence Of Polyamines On Pancreatic Volume or Enzyme Secresupporting
confidence: 59%
See 1 more Smart Citation
“…It could be shown that neither CCK-LP stimu lated pancreatic volume nor enzyme secre tion could be inhibited by giving simulta neously DFMO [11]. Similar to the studies concerning pancreatic growth, the applica tion of DFMO was not able to reduce the polyamine concentrations under a critical level.…”
Section: Influence Of Polyamines On Pancreatic Volume or Enzyme Secresupporting
confidence: 59%
“…The initial and transient inhibitory effect of DFMO on stimulated polyamines has also been described by Haarstad et al [ 11 ]. If the pancreatic polyamine concentration can hardly be reduced though the rate-limiting enzyme ornithine decarboxylase is effec tively inhibited, several other sources apart a de novo synthesis of polyamines have to be considered in order to maintain or to in crease the level of putrescine and spermidine [2] (fig.…”
Section: Evidence That Polyamines Are Involved In Induction Of Pancrementioning
confidence: 99%
“…While the important role of polyamine de novo synthe sis by ODC mainly during the induction of CCK-or camostate-induced pancreatic growth is well-defined [9,11,[13][14][15][16], nothing is known concerning the relevance of the various further intracellular regulatory mechanisms of the polyamine metabolism. The data of the present study clearly show three major findings.…”
Section: Discussionmentioning
confidence: 99%
“…The important role of the polyamine metabolism dur ing CCK or camostate-induced pancreatic growth was recently stressed by several authors [9,[11][12][13][14][15][16], In a for mer study we could clearly demonstrate the crucial role of polyamine de novo synthesis by ODC in CCK-and camostate-induced pancreatic growth mainly for the in duction of the trophic process [9,11]. Data concerning the role of further intracellular regulatory mechanisms of the polyamine metabolism during pancreatic growth are not available and especially the importance of the intercon version pathway as well as the oxidative degradation by amine oxidases remains to be determined.…”
mentioning
confidence: 99%
“…The role of the very high spermidine content in pancreas is not known, but it may be related to the extremely active protein synthesis going on in this particular tissue. The polyamines seem to be required for pancreatic growth and maturation [68], while their role in the exocrine function of the organ is less obvious [69].…”
Section: Pancreatitismentioning
confidence: 99%